Hubungan Pemberian ASI Eksklusif dengan Kejadian Alergi pada Bayi dan Anak Usia 7-60 Bulan di RSIA Kota Kediri - Suwoyo Suwoyo; Indah Rahmaningtyas (coba, 2016)
The prevalence of allergic reaction in this world reported to have increased dramatically in recent years. Currently, allergic becomes common disease for babies and infants. Infants younger than six months has limited choice of food be consumed. This limitation is due to the baby's immature gastrointestinal system. This will greatly facilitate the foreign protein to penetrate the baby's intestines, so it can cause allergies. One of the factors of allergies in babies and infants are breastfeeding, because protein contained in the breast milk is perfect for baby's body and almost entirely absorbed by the baby's digestive system. This study aims to determine the correlation of exclusive breastfeeding and allergic reaction in babies and infants (age 7-60 months) at RSIA Kediri City. The design used was a retrospective cohort. The population in this study were all mothers whose children examined aged 7-60 months in RSIA Kediri city. The sampling technique used is the Systematic Random Sampling, with a sample of 80 people. From this study showed that the majority of infants and children who are exclusively breastfed do not have allergies (68,75%). Through the Chi-Square correlation test, showed that there is a correlation between exclusive breastfeeding and allergic reaction in babies and infant age 7-60 months. This is because breast milk is basically naturally produced according to baby's needs, and contains proteins that helps to reduce the risk of allergies. Therefore, cooperation between health workers, the mother nearby, and public figures have a very important role in the success of exclusive breastfeeding. Key words : Exclusive Breastfeeding, Allergic Reaction, Babies and Infant